Growth Yield and Yield Attributes of Tomato (Lycopersicon esculentum Mill.) as Influenced by Indole Acetic Acid (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted at research field and laboratory of the Department of Crop Physiology and Ecology, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh during the period of December 2013 to April 2014. The experiment was laid out in two factors randomized complete block design with three replications including three concentrations of Indole Acetic Acid (0, 100 and 200 ppm) and three tomato varieties (BARI tomato 7, Manik and Ratan). Plant height, number of leaves and number of branches, days required for first flower initiation, days required for 50% flowering, days required for fruit setting, fruit cluster plant-1, fruit plant-1, weight tomato-1, yield plant-1, yield plot-1 and yield hectare-1 were significant influenced by the combined application of IAA and varieties of tomato. BARI Tomato-7 had the highest fruit yield with 100 ppm IAA and the lowest yield was observed in Ratan with 0 ppm IAA. IAA treated plots showed better performance for growth parameters and yield compared to control condition and 100 ppm IAA was more suitable than the 200 ppm IAA for higher yield of tomato cultivation. Among the treatment combinations, BARI Tomato-7 with 100 ppm IAA was superior, Ratan with 0 ppm IAA was inferior and BARI Tomato-7 with 200 ppm IAA, Manik with 200 ppm IAA and Ratan with 200 ppm IAA treated plots showed the intermediate results for yield and yield components.J. Environ. Sci. & Natural Resources, 8(1): 139-145 2015